Association between plant-based diet quality and chronic kidney disease in Australian adults - Jordan Stanford; Anita Stefoska-Needham; Kelly Lambert; Marijka J Batterham; Karen Charlton (Cambridge University Press, 2024)
Abstract Objective: To examine associations between three different plant-based diet quality indices, chronic kidney disease (CKD) prevalence and related risk factors in a nationally representative sample of the Australian population. Design: Cross-sectional analysis. Three plant-based diet scores were calculated using data from two 24-h recalls: an overall plant-based diet index (PDI), a healthy PDI (hPDI) and an unhealthy PDI (uPDI). Consumption of plant and animal ingredients from 'core' and 'discretionary' products was also differentiated. Associations between the three PDI scores and CKD prevalence, BMI, waist circumference (WC), blood pressure (BP) measures, blood cholesterol, apo B, fasting TAG, blood glucose levels (BGL) and HbA1c were examined. Setting: Australian Health Survey 2011-2013. Participants: n 2060 adults aged ≥ 18 years (males: n 928; females: n 1132). Results: A higher uPDI score was associated with a 3·7 % higher odds of moderate-severe CKD (OR: 1·037 (1·0057-1·0697); P = 0·021)). A higher uPDI score was also associated with increased TAG (P = 0·032) and BGL (P < 0·001), but lower total- and LDL-cholesterol (P = 0·035 and P = 0·009, respectively). In contrast, a higher overall PDI score was inversely associated with WC (P < 0·001) and systolic BP (P = 0·044), while higher scores for both the overall PDI and hPDI were inversely associated with BMI (P < 0·001 and P = 0·019, respectively). Conclusions: A higher uPDI score reflecting greater intakes of refined grains, salty plant-based foods and added sugars were associated with increased CKD prevalence, TAG and BGL. In the Australian population, attention to diet quality remains paramount, even in those with higher intakes of plant foods and who wish to reduce the risk of CKD.